A Transcriptome Approach Toward Understanding Fruit Softening in Persimmon - Jung, Jihye; Choi, Sang Chul; Jung, Sunghee; Cho, Byung-Kwan; Ahn, Gwang-Hwan; Ryu, Stephen B. (Frontiers in Plant Science, 2017)
Persimmon (Diospyros kaki Thunb.), which is a climacteric fruit, softens in 3-5 weeks after harvest. However, little is known regarding the transcriptional changes that underlie persimmon ripening. In this study, high-throughput de novo RNA sequencing was performed to examine differential expression between freshly harvested (FH) and softened (ST) persimmon fruit peels. Using the Illumina HiSeq platform, we obtained 259,483,704 high quality reads and 94,856 transcripts. After the removal of redundant sequences, a total of 31,258 unigenes were predicted, 1,790 of which were differentially expressed between FH and ST persimmon (1284 up-regulated and 506 down-regulated in ST compared with FH). The differentially expressed genes (DEGs) were further subjected to KEGG pathway analysis. Several pathways were found to be up-regulated in ST persimmon, including ‘amino sugar and nucleotide sugar metabolism’. Pathways down-regulated in ST persimmon included ‘photosynthesis’ and ‘carbon fixation in photosynthetic organisms’. Expression patterns of genes in these pathways were further confirmed using quantitative real-time RT-PCR. Ethylene gas production during persimmon softening was monitored with gas chromatography and found to be correlated with the fruit softening. Transcription involved in ethylene biosynthesis, perception and signaling was up-regulated. On the whole, this study investigated the key genes involved in metabolic pathways of persimmon fruit softening, especially implicated in increased sugar metabolism, decreased photosynthetic capability, and increased ethylene production and other ethylene-related functions. This transcriptome analysis provides baseline information on the identity and modulation of genes involved in softening of persimmon fruits and can underpin the future development of technologies to delay softening in persimmon.